Maintenance Management - Pedro García Márquez, Fausto; Papaelias, Mayorkinos (IntechOpen, 2020)
Maintenance is a critical variable in industry to achieve competitiveness. Therefore, correct management of corrective, predictive, and preventive politics in any industry is required. Maintenance Management considers the main concepts, state of the art, advances, and case studies in this topic. This book complements other subdisciplines such as economics, finance, marketing, decision and risk analysis, engineering, etc.The book analyzes real case studies in multiple disciplines. It considers the topics of failure detection and diagnosis, fault trees, and subdisciplines (e.g. FMECA, FMEA, etc.). It is essential to link these topics with finance, scheduling, resources, downtime, etc. to increase productivity, profitability, maintainability, reliability, safety, and availability, and reduce costs and downtime.This book presents important advances in mathematics, models, computational techniques, dynamic analysis, etc., which are all employed in maintenance management.Computational techniques, dynamic analysis, probabilistic methods, and mathematical optimization techniques are expertly blended to support the analysis of multicriteria decision-making problems with defined constraints and requirements.The book is ideal for graduate students and professionals in industrial engineering, business administration, industrial organization, operations management, applied microeconomics, and the decisions sciences, either studying maintenance or who are required to solve large, specific, and complex maintenance management problems as part of their jobs. The book will also be of interest to researchers from academia.